Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap Kepuasan Nasabah Pengguna Permata Me: Studi Kasus pada Nasabah Bank Permata Pengguna Aplikasi Permata Me - Arnetta Valentina Rigawara; Aditya Yudanegara (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study investigates the influence of product quality and service quality on consumer satisfaction among users of Permata Me, Bank Permata's digital banking application. As financial institutions increasingly shift to digital platforms, user satisfaction has become crucial for customer retention. This research employs a quantitative approach, collecting data from 400 active users of the Permata Me application through structured questionnaires. The data were analyzed using multiple linear regression to examine the relationship between product quality (encompassing functionality, reliability, and user interface), service quality (including responsiveness, assurance, and empathy), and overall customer satisfaction. Findings indicate that both product quality and service quality have a statistically significant positive impact on customer satisfaction. Product quality emerged as a stronger predictor, with features such as seamless transaction processing, fast performance, and an intuitive user interface being the most valued by users. This study contributes to the growing body of knowledge in the field of digital banking by emphasizing the dual importance of technical excellence and service excellence in mobile financial platforms.